Power Doppler ultrasonographic assessment of the joint-draining lymph node complex in rheumatoid arthritis: a prospective, proof-of-concept study on treatment with tumor necrosis factor inhibitors. Issue 1 (December 2016) - Manzo, Antonio; Benaglio, Francesca; Vitolo, Barbara; Bortolotto, Chandra; Zibera, Francesca; Todoerti, Monica; Alpini, Claudia; Bugatti, Serena; Caporali, Roberto; Calliada, Fabrizio; Montecucco, Carlomaurizio
Abstract Background Emerging research on the mechanisms of disease chronicity in experimental arthritis has included a new focus on the draining lymph node (LN). Here, we combined clinical-serological analyses and power Doppler ultrasound (PDUS) imaging to delineate noninvasively the reciprocal relationship in vivo between the joint and the draining LN in patients with rheumatoid arthritis (RA). Methods Forty consecutive patients refractory to conventional synthetic disease-modifying anti-rheumatic drugs were examined through parallel PDUS of the hand–wrist joints and axillary LNs and compared with 20 healthy subjects. A semiquantitative score for LN gray-scale (GS) parameters (nodal hypertrophy and cortical structure) and LN PD signal was developed. A 6-month follow-up study with serial sonographic assessments was then performed on initiation of tumor necrosis factor (TNF) inhibitors. Results PDUS analysis of RA axillary LNs revealed the existence of marked inter-individual heterogeneity and of quantitative differences compared with healthy individuals in both GS and PD characteristics. RA LN changes were plastic, responsive to anti-TNF treatment, and displayed a degree of concordance with synovitis activity in peripheral joints. However, low LN PD signal at baseline despite active arthritis was strongly associated with a poor clinical response to TNF blockade. Conclusions PDUS analysis of the draining LN in RA allows capture of measurable inter-individual differences and dynamic changes linked to the underlying pathologic process. LN and joint sonographic assessments are nonredundant approaches that may provide independent perspectives on peripheral disease and its evolution over time.